Nordic Artificial Intelligence Research and Development 4th Symposium of the Norwegian AI Society, NAIS 2022, Oslo, Norway, May 31 - June 1, 2022, Revised Selected Papers - Zouganeli, Evi; Yazidi, Anis; Mello, Gustavo; Lind, Pedro (Communications in Computer and Information Science,, 2022)
This book constitutes the refereed proceedings of the 4th Symposium of the Norwegian AI Society, NAIS 2022, held in Oslo, Norway, during May 31-June 1, 2022. The 11 full papers included in this book were carefully reviewed and selected from 17 submissions. They were organized in topical sections as follows: robotics and intelligent systems; ai in cyber and digital sphere; ai in biological applications and medicine; and towards new ai methods. This is an open access book.